COMPARATIVE PERFORMANCE OF ELITE SUGARCANE GENOTYPES IN 4TH CYCLE FOR CANE YIELD, YIELD COMPONENTS, QUALITY AND BORER COMPLEX INFESTATION - S. Junejo; M. Chohan; A. A. Junejo; G. M. Kaloi; R. N. Panhwar; M. Y. Arain (Journal of Animal and Plant Sciences, 2009)
The study was conducted at National Sugar Crops Research Institute (NSCRI) experimental farm Thatta during 2005-06. The performance of twenty-two elite sugarcane genotypes developed from exotic fuzz (true seed) of USA origin along with two standard varieties Thatta-10 and BL-4 as local check was evaluated in 4th cycle. The results showed that there were significant differences amongst the genotypes for the traits under study. The genotype HoTh-518 exhibited maximum average cane yield (115.0 t ha-1) with fairly better commercial cane sugar CCS (14.19%) followed by HoTh-544 and HoTh-548 with at par average cane yield (108 t ha-1) and maximum commercial cane sugar (CCS) (14.25%). The genotype HoTh-517 also showed comparatively good performance with average cane yield (107 t ha-1) and sufficient CCS (13.91%) followed by HoTh-514 and HoTh-550 with similar cane yield of 105 t ha-1 and better CCS of 14.09 and 14.15%, respectively, against Thatta-10 and BL-4 (local check) which showed average cane yield of 98.0 and 97.0 t ha-1 and CCS of 13.49 and 13.39%, respectively. However, rest of the genotypes exhibited comparatively lower results in terms of average cane yield and quality against the check varieties. The bore complex infestation data revealed that all the genotypes along with check varieties remained less susceptible to borer infestation except HoTh-529, HoTh-520, HoTh-523 and HoTh-537 which were observed highly susceptible with mean infestation of 14.08, 13.15 and 12.77%, respectively while, HoTh-519 and HoTh-540 were susceptible to borer complex attack with mean infestation of 10.21 and 10.19%, respectively.
Keywords: Sugarcane; true seed; genotypes; performance; development.